2016
DOI: 10.1039/c5nj03641k
|View full text |Cite
|
Sign up to set email alerts
|

A block copolymer containing PEG and histamine-like segments: well-defined functions for gene delivery

Abstract: The delivery of genetic materials to cells provides a promising treatment approach to many genetic diseases. The rational structural design for reducing the toxicity while improving transfection efficiency is an important strategy for the development of safe and highly efficient polycation gene vectors. In this study, a novel block copolymer composed of PEG and cationic histamine-like segments was synthesized via reversible addition-fragmentation chain transfer (RAFT) polymerization and subsequently the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Our previous reports demonstrated that polyplexes [45] and nanoplexes [24] with a PEG shell, and which condense DNA via PAMPImB, are highly stable in physiological media. We assessed magnetic nanoplex stability in different media by DLS (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous reports demonstrated that polyplexes [45] and nanoplexes [24] with a PEG shell, and which condense DNA via PAMPImB, are highly stable in physiological media. We assessed magnetic nanoplex stability in different media by DLS (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxicity of composite nanoparticles often depends on their size and surface properties [46]. PEG- b -PAMPImB is a low cytotoxic polymer because PEG and the cationic histamine-like segment have high biocompatibility, as shown in our previous report [45]. The formation of micelle-like core–shell structures upon attachment to Fe 3 O 4 @Au further decreases cytotoxicity, as the PEG outer corona shields the inner shell of the cationic histamine-like segment.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations